Success Factors for Female Entrepreneurs in Small and Medium Micro Enterprises (SMEs) - Fish Crackers Business - Wahyu Hati, Shinta; Syarifah, Syarifah (Riviera Publishing, 2023)
This study aims to determine the success factors of female entrepreneurs in Small and Medium Enterprises (SMEs) of fish crackers in Moro District, Karimun Regency—data collection techniques using a questionnaire. The data analysis method used in this research is descriptive analysis and confirmatory factor analysis (CFA). The results of this study indicate that of the 28 indicators analyzed, eight factors can be formed, namely personality factors, family support, Technology, Education, Quality of Nature, Confidence, Government Support, and Gender Discrimination. At the same time, the most dominant factor in the success of women entrepreneurs in Moro District, Karimun Regency, is the Personality factor, with a variance value of 28.029%. This research has implications that emphasize encouraging and supporting women's participation in the SME sector. Identifying success factors for women entrepreneurs can help design targeted training and capacity-building programs. Raising awareness among local communities about the economic and social contributions of SMEs led by women can lead to greater support and appreciation for business.